Desain Embung Berbantu Komputer Di Kali Sabi Kota Tangerang Banten: Computer Aided Design for Water Retention in Kali Sabi Tangerang City Banten - Moch Ridwan Widiansyah; Budi Indra Setiawan (Departemen Teknik Sipil dan Lingkungan, IPB University, 2020)
The problem of flooding in the city of Tangerang is a problem that requires further treatment. Improper management of water resources is one of the factors that cause flooding which results in losses for the community.The activity carried out as an effort to prevent floods is the creation of water retention. The purpose of this research is to know the flood discharge in Kali Sabi, know volume that must be accommodate, determine the capacity for water retention, produce an effective technical water retention design, and obtain an estimated cost of making the water retention. This research was conducted in April-July 2020 in Uwung Jaya Village, Tangerang City using topographic and rainfall data for 12 years. Rain distribution using the Log Pearson III . The results of the analysis revealed that the effective rainfall of the 5-year return period was 66.314 mm with a maximum flood discharge of 83.69 m³. Volume runoff that had to be overcome was 1084.64 m³. The effective storage capacity of the water retention is ± 1975 m³ with an area of ± 525 m², with construction materials, reinforced concrete with K-225 quality and 10 mm diameter reinforcement. Water retention has two steel sliding gates at the inlet and outlet. Construction of the water retention is estimated to cost Rp. 813,839,000.00.